Interdisciplinární Evropská doporučení metabolické a bariatrické chirurgie - Fried, M; Yumuk, V; Oppert, J M; Scopinaro, N; Torres, A; Weiner, R; Yashkov, Y; Frühbeck, G (Rozhledy v chirurgii, 2014)
In 2012, an outstanding expert panel derived from IFSO-EC (International Federation for the Surgery of Obesity - European Chapter) and EASO (European Association for the Study of Obesity), composed by key representatives of both Societies including past and present presidents together with EASOs OMTF (Obesity Management Task Force) chair, agreed to devote the joint Medico-Surgical Workshop of both institutions to the topic of metabolic surgery as a pre-satellite of the 2013 European Congress on Obesity (ECO) to be held in Liverpool given the extraordinarily advancement made specifically in this field during the past years. It was further agreed to revise and update the 2008 Interdisciplinary European Guidelines on Surgery of Severe Obesity produced in cooperation of both Societies by focusing in particular on the evidence gathered in relation to the effects on diabetes during this lustrum and the subsequent changes that have taken place in patient eligibility criteria. The expert panel composition allowed the coverage of key disciplines in the comprehensive management of obesity and obesity-associated diseases, aimed specifically at updating the clinical guidelines to reflect current knowledge, expertise and evidence-based data on metabolic and bariatric surgery.
Keywords: bariatrická chirurgie; obezita; Diabetes Mellitus; Obesity, Morbid; diabetes mellitus; Humans; lidé; Obesity; morbidní obezita; Bariatric Surgery